INTERACTIONS BETWEEN HEALTH AND AGRICULTURAL OUTPUT ON ECONOMIC GROWTH IN NIGERIA - Ogunbadejo, Hussain Kehinde; Aisha, Zubair (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
This paper examines the Interactions between health and agricultural output on economic growth in Nigeria using annual time series dataset spanning 1980 to 2018. Body mass index was proxied for health while the real Gross Domestic Product captures economic growth. The two stage Least Squares approach was adopted in the analysis after testing for unit root and cointegration among variables. Results indicate that the interactive variable was positively signed and statistically significant at a 5 percent level both physical and labour exert a significant positive impact on economic growth in Nigeria. Specifically, body mass index and agricultural output significantly spur economic growth. The paper recommends, amongst others, that government should strive a programme that will not only encourage agricultural output but also enhance the health facilities in the country at all levels. Government should increase allocation to health and agriculture sectors in the country for optimal performance of the economy.